Gentrification around the World, Volume I. Gentrifiers and the Displaced. - (:unkn) unknown (Palgrave Macmillan, 2020)
Bringing together scholarly but readable essays on the process of gentrification, this two-volume collection addresses the broad question: In what ways does gentrification affect cities, neighborhoods, and the everyday experiences of ordinary people? In this first volume of Gentrification around the World, contributors from various academic disciplines provide individual case studies on gentrification and displacement from around the globe: chapters cover the United States of America, Spain, Brazil, Sweden, Japan, Korea, Morocco, Great Britain, Canada, France, Finland, Peru, India, Indonesia, Pakistan, Syria, and Iceland. The qualitative methodologies used in each chapter—which emphasize ethnographic, participatory, and visual approaches that interrogate the representation of gentrification in the arts, film, and other mass media—are themselves a unique and pioneering way of studying gentrification and its consequences worldwide.
Keywords: Stadtgeographie; Segregation; Gentrifizierung; Auswirkung; Bewohnerstruktur; Nachbarschaft; Verdrängung; Stadterneuerung; Aufwertung; Stadtsoziologie; Problemdarstellung; Massenmedien; Fallstudie; Internationaler Vergleich